Filamentous recombinant human Tau activates primary astrocytes via an integrin receptor complex - Peng Wang (Nature Portfolio, 2021)
The mechanisms underlying the transmission of Tau in astrocytes are unclear. Here, the authors show that the entry of filamentous recombinant human Tau into astrocytes via the integrin αV/ β1 complex stimulates integrin signaling, resulting in activation of NFκB and astrocyte conversion towards a neurotoxic state.